Optimisation of Geotechnical Properties of Spent Ore for Road Construction in Ghana - BERNARD OFOSU; Micheal Affam; Farouk Omar Uman; Vincent Acquah Bondzie (Lowland Technology International, 2021)
Mining operations generate large volume of wastes (spent ore) and due to its potential toxic nature, it is managed in accordance to very strict environmental regulations in Ghana. The spent ore can be reutilized as a construction material especially for road, however, due to its granular nature, it is not possible to compact the materials to achieve the required strength for engineering purposes. Laterite which is abundantly found in Ghana was used to improve the engineering properties of spent ore for road base and subbase construction. The laterite was added to the spent ore in range of 10% to 50% to form composites. Physical and engineering laboratory tests including moisture content, Atterberg Limits, compaction and Californian Bearing Ratio were conducted on the composites in accordance with British Standards. The results show that the Liquid Limit of the composites are between 18.7% and 30%, the Plasticity Index are between 1.3% and 11.3%. The soaked CBR values are between 32% and 62%, the unsoaked values are between 31% and 64%. The results show that, 30% addition of the laterite will improve the spent ore for only subbase construction based on Ghana Highway Authority standards for base and subbase materials in Ghana.